Design and Off-Design Calculations of Single Spool Turbojet Engine Performance - I.G.A. Uttariyani; Diki Diki; Widiasih Widiasih; Muhamad Dahsyat; Hasoloan Siregar (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The research project of the Open University and the National Research and Innovation Agency is taking place at the Open University, to design a turbojet engine that produces the targeted thrust at a speed (M), the height of the pilot with the rotational speed (RPM) set in the research activity. This paper presents the design of the performance of a single spool turbojet engine at Design Point (DP) and Off-Design Point (ODP) conditions. The calculation of the DP condition is solved using equations that have been provided in the literature, to obtain the appropriate mass flow rate. In the calculation of ODP with variations in temperature, pressure, Mach numbers using the C.N.Reffold semi-dimensional mass flow (SDMF) method to find the compressor pressure ratio. The purpose of this article is to present an ODP calculation that avoids the use of